Re-embedding the economy in nature and society: Seven theses on the socio-ecological reorientation of the economy in times of Covid-19 and the climate crisis - Reinhard Loske (Cusanus Hochschule für Gesellschaftsgestaltung, Institute für Ökonomie und für Philosophie, 2020)
This paper reflects on the links between the current COVID-19-crisis and the climate and biodiversity crises. It argues that the present pandemic and nonsustainable development on a global scale have similar roots: from ignoring natural boundaries to denying scientific facts, from over-globalisation to a one-sided economic understanding of public services, from a systematic undervaluation of caring activities to consumerism and growth-fetishism. As result our societies became less resilient and more vulnerable over the last decades. Various policy proposals to overcome these undesirable developments are presented in the paper, including selective de-globalisation, regionalization, circular economy, global fairness, the strengthening of public goods and a strategy of democracydriven "glocalisation".
Keywords: B52; B59; D62; F02; F41; F55; F60; G38; Q01; Q57; Q58; 330; COVID-19-crisis; climate and biodiversity crises; common roots; re-embedding the economy in nature and society; global fairness; "glocalisation"